Analysis of Variance in the Beverage Filling Process: An Application of One-Way ANOVA to Product Lines at Seven-Up Bottling Company, Kaduna, Nigeria - Chinedu Samuel Onyedika (Darul Yasin Al Sys, 2026)
Consistency in beverage filling is essential for regulatory compliance, product quality, and consumer confidence, particularly in high-volume bottling operations involving multiple product lines. This study investigated whether mean net-content filling values differed significantly across five product lines—7UP, Mirinda Orange, Mountain Dew, Pepsi, and Teem Bitter Lemon—at the Seven-Up Bottling Company Kaduna Plant. Net-content filling data were collected during morning, afternoon, and night production shifts on selected production days between July and August 2021, yielding 75 observations, with 15 observations obtained for each product. A one-way analysis of variance was conducted to compare mean filling values across the five product lines, followed by Tukey simultaneous comparisons and Fisher individual tests for pairwise differences in means. The analysis revealed no statistically significant difference in mean filling values across the product lines, F = 0.30, p = .879, at α = .05. The post hoc analyses corroborated this result, as all adjusted pairwise p-values exceeded the .05 significance threshold. Accordingly, the null hypothesis that the five product lines had equal mean filling values was not rejected. These findings indicate that the filling process did not generate statistically different filling outcomes across product types during the study period. The observed filling-related variation is therefore more consistent with common-cause process variation than with product-specific assignable causes. The study contributes empirical evidence for strengthening statistical quality-control practices in beverage production and underscores the importance of continuous process monitoring to maintain net-content consistency across product lines.